Treatment Adherence among People with Drug-resistant Tuberculosis in Lagos Nigeria: The Effects of Stigma, Resilience, Social Support, and Temporal Discounting - Olusola Adedeji Adejumo; Olusoji James Daniel; Champaklal Jinabhai; Firoza Haffejee (International Journal of Mycobacteriology)
Background: This study assessed the effects of social support, resilience, temporal discounting, and stigma on medication adherence among people with drug-resistant tuberculosis (PwDR-TB) in Lagos, Nigeria. Methods: A cross-sectional study was conducted between September and December 2023 among 203 adults on DR-TB treatment. The Morisky Medication Adherence Scale-8, Redwood DR-TB scale, multidimensional scale of perceived social support, brief resilience scale, and deferment of gratification scale were used to assess adherence, stigma, social support, resilience, and temporal discounting respectively. Pearson’s correlation and hierarchical linear regression analysis were conducted to explore the relationships between adherence, stigma, social support, resilience, and temporal discounting. Results: The prevalence of low, medium, and high adherence was 20.7%, 73.4%, and 5.9%, respectively. Adherence was positively associated with social support (B = 0.380, P < 0.001), resilience (B = 0.210, P < 0.001), and temporal discounting (B = 0.364, 0 < 0.001) and negatively associated with stigma (B = −0.317, P < 0.001). Temporal discounting made a higher significant contribution (B = 0.343, P < 0.001) in predicting adherence than social support (B = 0.187, P = 0.005), resilience (B = 0.175, P = 0.002) and stigma (B = −0.317, P < 0.001). Conclusion: Patient-centred interventions that promote social support, resilience, and temporal discounting are urgently needed to enhance adherence among PwDR-TB. Stigma reduction strategies are required at all levels.